2007
DOI: 10.1080/01443610601016909
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric outcome in women complaining of reduced fetal movements

Abstract: Premature ovarian failure (POF) is gonadal failure before the age of 40 years. Several rare causes have been discovered yet we still fail to identify the cause in many cases. Although it was once thought to be a permanent condition, a substantial number of patients experience spontaneous remissions and even pregnancy. HRT remains the cornerstone of treatment and the only proven method of achieving pregnancy in these patients is by ovum donation. New alternatives to HRT and fertility preservation are under deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 6 publications
7
44
2
Order By: Relevance
“…In addition, the result that the ratio of placental abruption before 37 weeks increased with gestational age was consistent with a previous study (Ananth and Wilcox 2001). Our result also indicated that DFM was the most common reason for visiting OPD, which is consistent with previous studies (Olesen and Svare 2004;Sinha et al 2007). Excessive delay in maternal reporting of DFM is associated with stillbirths (Grant et al 1989;Frøen et al 2001).…”
Section: Discussionsupporting
confidence: 82%
“…In addition, the result that the ratio of placental abruption before 37 weeks increased with gestational age was consistent with a previous study (Ananth and Wilcox 2001). Our result also indicated that DFM was the most common reason for visiting OPD, which is consistent with previous studies (Olesen and Svare 2004;Sinha et al 2007). Excessive delay in maternal reporting of DFM is associated with stillbirths (Grant et al 1989;Frøen et al 2001).…”
Section: Discussionsupporting
confidence: 82%
“…The use of kickcharts increased attendences for assessment of fetal wellbeing (15.5% vs 9.8%) and was associated with a 2.6 fold increased obstetric intervention rate (Heazell et al, 2005;Whitty et al, 1991). Another report demonstrated higher intervention rates (32% vs 21%) and caesarean section rates (24% vs 14%) (Sinha et al, 2007).…”
Section: Fetal Movement Counting (Count-to-ten Kickcharts)mentioning
confidence: 97%
“…Up to 5% of women will re-present with reduced FM (Sinha et al, 2007). If the perception of reduced FM persists, consideration should be given to other causes such as fetal structural anomalies (4.3%), anaemia or feto-maternal haemorrhage.…”
Section: Management Of Second and Subsequent Presentationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fetus responds to chronic hypoxia by conserving energy and the subsequent reduction of fetal movements is an adaptive mechanism to reduce oxygen consumption. A number of 11-29% of women presenting with reduced fetal movements carry a small for gestational age (SGA) fetus below the 10 th centile 2,3 .…”
mentioning
confidence: 99%